Identifying risks, costs, and lessons from ARENA‐funded off‐grid renewable energy projects in regional Australia. (10th April 2018) - Herteleer, Bert; Dobb, Anthony; Boyd, Olivia; Rodgers, Steven; Frearson, Lyndon
Abstract: The Australian Renewable Energy Agency (ARENA) has provided grant funding to 18 off‐grid and fringe‐of‐grid renewable energy projects under the Regional Australia's Renewables (RAR) program since 2013. This program was designed to address real and perceived risks associated with early stage, precommercial renewable energy development and provide a foundation of demonstration projects to enable the development of a competitive renewable energy sector. These projects range from low to high renewable energy fractions at megawatt scale in remote regions of Australia and encompass a variety of sectors, such as mining, tourism, and remote communities. All projects use photovoltaic as a key technology, often supplemented by additional technologies. The experience from these projects shows that land acquisition, technical integration, stakeholder engagement, and access to finance are among the main reasons for project delivery delays. A qualitative assessment for the remoteness premium is given, based on a comparison of ARENA‐funded on‐grid and off‐grid projects. This indicates that the structural barriers of governance, supply chains, and finance need to be tackled further to lower soft costs. One of the key enablers for future lower renewable energy costs is ARENA's Knowledge Sharing model, through which the funding agency is recompensed by data and information that is provided to the market and increases the impact of ARENA funding. Abstract : ARENA has provided grant funding to 18 off‐grid and fringe‐of‐grid renewable energy projects under its RAR program since 2013. These projects show that land acquisition, technical integration, stakeholder engagement, and access to finance are among the main reasons for project delivery delays, and a remoteness premium is shown by comparing these projects with utility‐scale on‐grid projects. ARENA's Knowledge Sharing model allows the funding agency to be recompensed by data and information from funded projects, and increases its impact.